2007
DOI: 10.1128/aem.00228-07
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Infections, Cryptic Diversity, and Vector-Borne Pathogens: Evidence from Polygenis Fleas and Bartonella Species

Abstract: Coinfections within hosts present opportunities for horizontal gene transfer between strains and competitive interactions between genotypes and thus can be a critical element of the lifestyles of pathogens. Bartonella spp. are Alphaproteobacteria that parasitize mammalian erythrocytes and endothelial cells. Their vectors are thought to be various biting arthropods, such as fleas, ticks, mites, and lice, and they are commonly cited as agents of various emerging diseases. Coinfections by different Bartonella str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 59 publications
2
48
2
1
Order By: Relevance
“…These results suggest that fleas harbor richer Bartonella assemblages than their hosts, and that mammals may be exposed to a wider spectrum of Bartonella than those causing bacteremia. Abbot et al (2007) reported similar patterns of coinfection in rodent fleas and suggested that host specialization may account for mammal-Bartonella relationships. Bartonellae can 'jump' among host species (Jardine et al, 2005;Bai et al, 2007) and fleas have been implicated in facilitating such events (Bai et al, 2007).…”
mentioning
confidence: 63%
“…These results suggest that fleas harbor richer Bartonella assemblages than their hosts, and that mammals may be exposed to a wider spectrum of Bartonella than those causing bacteremia. Abbot et al (2007) reported similar patterns of coinfection in rodent fleas and suggested that host specialization may account for mammal-Bartonella relationships. Bartonellae can 'jump' among host species (Jardine et al, 2005;Bai et al, 2007) and fleas have been implicated in facilitating such events (Bai et al, 2007).…”
mentioning
confidence: 63%
“…Co-infection of hosts and vectors with more than one Bartonella species or genotype is a well-known phenomenon (Gurfield et al, 1997;Abbot et al, 2007;Breitschwerdt, 2008;Chan and Kosoy, 2010). However, questions relating to the composition, the potential interchange of bartonellae variants between hosts and vectors and the overall diversity of bartonellae in either environment are not fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This genotype tended to dominate several flea-associated bartonellae infections (Table 2). With the development of the molecular techniques, the detection of concurrent multiple infections became more feasible (Abbot et al, 2007). The 454-pyrosequencing assay provided the benefit of receiving the maximal number of amplicons that could be detected in each sample (Dowd et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations